Wavelet packet analysis of blasting vibration signal of mountain tunnel - Huang, Dan; Cui, Shuo; Li, Xiaoqing (Soil dynamics and earthquake engineering (1984), 2019)
Using drilling and blasting method to construct the Mountain tunnel, it is important to monitoring and analysis of blasting seismic wave. The research of simple characteristics of blasting vibration wave such as amplitude, frequency, duration in the previous study, it is lack the detailed characteristics of blasting seismic waves such as frequency distribution characteristics of blasting seismic wave, blasting energy distribution. Thus, Fourier transform and wavelet packet transform are both used to analysis the time - frequency characteristics of measured vibration signal, and the characteristics of its multi-frequency band and energy distribution are discussed. The blasting vibration with the blasting charge of 79.2 kg are did, and the wave are received distance blast source 10 m, 25 m, 40 m. The maximum three vector resultant velocity at 10 m is 5.84 cm/s, which meets the specification safety requirement. Analysis of blasting vibration signals of vertical axis which distance blast source 10 m, the main frequency of this signal is 101.9 Hz, and the relative amplitude is 2382 use by Fourier transform. The Wavelet packet analysis show that, blasting vibration signal has obvious energy distribution characteristics of multi-frequency band. The dominant frequency band (31.25 Hz~125.00 Hz) contains more than 70% of the energy of vibration signal. •The blasting vibration test was carried out on the Xiaobei No.1 tunnel.•Fourier transform and wavelet packet analysis are performed on the same signal.•The highest frequency band was found in the first 10 bands.